2022
DOI: 10.1038/s41598-022-15413-1
|View full text |Cite
|
Sign up to set email alerts
|

Human enteric adenovirus F40/41 as a major cause of acute gastroenteritis in children in Brazil, 2018 to 2020

Abstract: Human adenovirus (HAdV) types F40/41 have long been recognized as major viral agents of acute gastroenteritis (AGE) in children. Despite this, studies on HAdV molecular epidemiology are sparse, and their real impact is likely under-estimated. Thus, our goal was to investigate HAdV incidence, enteric and non-enteric types circulation, co-detections with rotavirus and norovirus and DNA shedding in stool samples from inpatients and outpatients from eleven Brazilian states. During the three-year study, 1012 AGE st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 65 publications
4
8
1
Order By: Relevance
“…[23][24][25] Incubation ranges from 2 to 14 days 26 HAdVs can affect people of all ages and usually cause mild, self-limiting infections in immunocompetent individuals, manifesting diverse diseases according to tissue tropism depending on the type. 24,27 But, people sometimes die of adenovirus infections, primarily patients with immunodeficiency 28,29 and, rarely, previously healthy people. 30,31 A recent review of 65 years of the seroprevalence of HAdVs, based on various studies, showed that frequency ranged from 2%…”
Section: Adenovirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Incubation ranges from 2 to 14 days 26 HAdVs can affect people of all ages and usually cause mild, self-limiting infections in immunocompetent individuals, manifesting diverse diseases according to tissue tropism depending on the type. 24,27 But, people sometimes die of adenovirus infections, primarily patients with immunodeficiency 28,29 and, rarely, previously healthy people. 30,31 A recent review of 65 years of the seroprevalence of HAdVs, based on various studies, showed that frequency ranged from 2%…”
Section: Adenovirus Infectionmentioning
confidence: 99%
“…Adenoviruses can spread from an infected person to others via droplets of respiratory or ocular secretions, the air by coughing and sneezing, through close personal contact (such as touching or shaking hands), touching an object or surface with adenoviruses on it and then touching one's mouth/nose/eyes, contact with stool or urine 23–25 . Incubation ranges from 2 to 14 days 26 HAdVs can affect people of all ages and usually cause mild, self‐limiting infections in immunocompetent individuals, manifesting diverse diseases according to tissue tropism depending on the type 24,27 . But, people sometimes die of adenovirus infections, primarily patients with immunodeficiency 28,29 and, rarely, previously healthy people 30,31 …”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%
“…From 2003 to 2006, Banyai et al (22) investigated diarrheic patients of Hungry by PCR for adenovirus infection; type Ad41 had been circulating all four years, but type Ad40 had only been found in 2003 and 2004. The incidence of adenovirus infection among gastroenteritis patients has been attributable to both types 40 and 41 of adenovirus, but recent investigations indicate that type 40 infection has declined and type Ad41 infection has increased (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Out of 74 cases of acute hepatitis of unknown aetiology with detected adenovirus, 18 patients were identified by molecular tests as serotype F41, and a few others were serotype F40[ 27 ]. This finding may indicate that enteric adenoviral infection may be related to hepatic infection by means of the gut-liver axis, a topic that warrants further research[ 28 ].…”
Section: Adenovirus Hepatotropic Effectsmentioning
confidence: 99%